The Effect of POGIL Model Toward Science Process Skills and Physics Acquisition of Student - Elfrida Toyo; Sudi Dul Aji; Chandra Sundaygara (Universitas Lambung Mangkurat, 2019)
This research aims to determine the differences in the Process Oriented Guided Inquiry Learning (POGIL) model toward science process skills and physics acquisition of students. The method used in this study was a quasi-experimental research design with posttest-only involving 64 students as samples. The research sample was chosen based on a purposive sampling technique. Instruments for measuring science process skills in the way of process skills assessment sheets and physics concept acquisition in the form of multiple-choice tests. Data analysis used is two-way ANOVA. The results showed that there were differences in science process skills between students who learned using the POGIL model and students who learned using the direct instruction model with a value of F=10.207 (p>0.05). There were differences in the mastery of concepts between students learning using the POGIL model and students who learned using a direct instruction model with F=17.771 (p>0.05) There is an interaction between the POGIL model and science process skills towards mastery of concepts with a value of F= 5.660 (p>0.05).